Understanding the Factors Influencing Pedestrian Crossing Behavior and Its Effect on Road Performance in Port Harcourt City (Global Journals of Research in Engineering, 2023)
In Port Harcourt city the design of roads does not adequately accommodate pedestrians leading to ongoing conflicts as motorists and pedestrians try to share the limited space on the roads There is little response time to control vehicles in Port Harcourt making pedestrian crossing behavior at intersections and midblock crossings significantly more complicated All of these problems highlight to the need for additional research into pedestrian crossing behavior at major roads in Port Harcourt This study s primary goal is to find out the factors influencing pedestrian crossing behavior at signalized intersections and midblock crossings and also its effect on road performance For this reason 520 questionnaires were developed and shared among road users drivers and pedestrians to determine the factors influencing pedestrian crossing behavior Also traffic survey was conducted using a video camara The questionnaires were analyzed using the Likert scale to identify factors that are critical In addition the level of service LOS was used to assess the effect on congestion Result from this study revealed that age lack of crossing facilities location of crossing facility education and awareness are critical factors influencing pedestrian crossing behavior while gender is not a critical factor and the use of mobile phone is a neutral factor The LOS shows the volume to capacity ratio V C value of the road segments ranging from 0 72 to 0 97 which means smooth to low traffic flow with an affected speed and high vehicular density This is a true reflection of the roads in Port Harcourt Also at signalized intersections it was observed that 73 19 of pedestrians comply to signal indications
Keywords: pedestrian crossing behavior; congestion; signalized intersection; midblock crossing